A novel pathogenesis-related protein (LcPR4a) from lentil, and its involvement in defence against Ascochyta lentis - VAGHEFI, Niloofar; MUSTAFA, Barkat; DULAL, Nabeen; SELBY-PHAM, Jamie; TAYLOR, Paul; FORD, Rebecca (Phytopathologia Mediterranea, 2013)
A novel pathogenesis-related protein 4 (PR4) encoding gene, LcPR4a, was induced in Lens culinaris following Ascochyta lentis infection. LcPR4a encodes a predicted 146 amino acid protein of 15.8 kDa. The putative LcPR4a protein belongs to the class II PR4 family and has close phylogenetic affinity to PR4 proteins from related species. qPCR analysis revealed differential expression of the LcPR4a gene upon Ascochyta lentis infection in both resistant and susceptible cultivars. This, combined with preliminary in vitro antifungal assays of the recombinant protein expressed in E. coli, suggests the potential important role of LcPR4a in the defence response of lentil to Ascochyta lentis attack.